2019
DOI: 10.3390/app9194012
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion Control of Snake-Like Robot with Rotational Elastic Actuators Utilizing Observer

Abstract: The purpose of this paper is designing a head control system capable of adapting to passive side-slipping. The environments in which snake-like robots are expected to be utilized generally have ground surface conditions with nonuniform frictional coefficients. In such conditions, the passive wheels of the snake-like robot have a chance of side-slipping. To locomote the snake-like robot dexterously, a control system which adapts to such side-slipping is desired. There are two key points to realizing such a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Under these conditions, the snake-like robot has the potential to experience body skidding. Some studies based on this assumption have been reported [5,6,7,8,9]. For example, in [9], body skidding is represented by a hybrid model to realize a propulsion control system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the snake-like robot has the potential to experience body skidding. Some studies based on this assumption have been reported [5,6,7,8,9]. For example, in [9], body skidding is represented by a hybrid model to realize a propulsion control system.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies based on this assumption have been reported [5,6,7,8,9]. For example, in [9], body skidding is represented by a hybrid model to realize a propulsion control system. The hybrid model method requires accurate model switching for the control system to properly determine the control input.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, some scholars have put considerable effort into understanding the snake's movement and trying to create a robot that mimics it. The steps involved are to first study the snake's motion curve and then to apply mechanical operation principles to create snake-type motion [8]. These steps include deriving the velocities of different snake segments to perform rectilinear motion [9][10][11], using the position of the motor and leaning against the rotation of the wheel to cause the snake-shaped robot to move forward [12], and using Watt-I planar linkage mechanism to control a biped water-running robot to generate propulsion force [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al have implemented slope climbing control by adjusted amplitude of the Serpenoid Curve via a simulator [4]. In our previous study, we have designed a servo control system for tracking to the Serpenoid Curve [5]. Relative researches with respect to propulsive control use difference of the friction forces between the propulsive direction and the normal direction also have been reported [6,7].…”
Section: Introductionmentioning
confidence: 99%